A butterfly-shaped water tetramer in a Cu4 complex supported by a hydrazone ligand: Synthesis, crystal structure, magnetic properties, and quantum chemical study - Banerjee, Sambuddha; Sen, Soma; Chakraborty, Joy; Butcher, Ray J.; García, Carlos J.Gómez; Puchta, Ralph; Mitra, Samiran (Australian Journal of Chemistry, 2009)
A potentially tetradentate NOOO donor hydrazone ligand, LH2 (condensation product of benzhydrazide with O-vanillin) generates a tetranuclear CuII complex [Cu4(L)4]·4H2O (1), whose void spaces are occupied by water tetramers presenting a 'butterfly' conformation with the highest dihedral angle reported to date, as revealed by its X-ray crystal structure. 1 has also been characterized using various spectroscopic techniques, including IR, UV-vis, and elemental analysis. Variable temperature magnetic susceptibility measurements reveal the presence of moderate antiferromagnetic intra-tetramer coupling between the four Cu II centres connected through simple oxo groups of the hydrazone ligand with two different coupling constants (J1 = -61.7(3) cm -1 and J2 = -92(1) cm-1) corresponding to the two different CuII tetramers identified in the X-ray structure. We also report a quantum chemical study (MP2(full)/6-311+G(3df,2p)//B3LYP/6- 311+G(3df,2p)) to calculate the stability of the water tetramers. © 2010 CSIRO.
CRIS-Team Scopus Importer:2026-01-22